Comparison of Glenohumeral Contact Pressures and Contact Areas After Posterior Glenoid Reconstruction With an Iliac Crest Bone Graft or Distal Tibial Osteochondral Allograft. (November 2014) - Frank, Rachel M.; Shin, Jason; Saccomanno, Maristella F.; Bhatia, Sanjeev; Shewman, Elizabeth; Bach, Bernard R.; Wang, Vincent M.; Cole, Brian J.; Provencher, Matthew T.; Verma, Nikhil N.; Romeo, Anthony A.
Background: Posterior glenoid bone deficiency in the setting of posterior glenohumeral instability is typically addressed with bone block augmentation with iliac crest bone grafts (ICBGs). Reconstruction with fresh distal tibial allograft (DTA) is an alternative option, with the theoretical advantages of restoring the glenoid articular surface, improving joint congruity, and providing the biological restoration of articular cartilage loss. Hypothesis: Reconstruction with an ICBG and DTA would more effectively restore normal glenoid contact pressures, contact areas, and peak forces when compared with the deficient glenoid. Study Design: Controlled laboratory study. Methods: Eight fresh-frozen human cadaveric shoulders were tested in 4 conditions: (1) intact glenoid, (2) 20% posterior-inferior defect of the glenoid surface area, (3) 20% defect reconstructed with a flush ICBG, and (4) 20% defect reconstructed with a fresh DTA. For each condition, a 0.1 mm–thick dynamic pressure-sensitive pad was placed between the humeral head and glenoid. A compressive load of 440 N was applied for each condition in the following clinically relevant arm positions: (1) 30° of humeral abduction, (2) 60° of humeral abduction, and (3) 90° of flexion–45° of internal rotation (FIR). Glenohumeral contact pressures (kg/cm 2 ), contact areas (cm 2 ), and joint peak forces (N) were compared. Results: Glenoid reconstruction with DTA resulted in significantly higher contact areas than the 20% defect model at 30°, 60°, and FIR at the time of surgery ( P < .01 in all cases). The intact state exhibited significantly higher contact areas than the defect in all positions, significantly higher contact areas than the ICBG in all positions, and significantly higher contact areas than the DTA at 30° ( P < .05 in all cases). The intact state experienced significantly lower contact pressures than the defect at 60° and FIR, while reconstruction with both a DTA and ICBG resulted in significantly lower contact pressures than the defect at 60° ( P < .05 in all cases). There were no differences in contact pressures when comparing both the DTA and ICBG to the intact glenoid ( P > .05 in all cases). There were no differences in peak forces between the groups, for any of the conditions, in any of the positions ( P > .05 in all cases). Conclusion: Reconstruction of posterior glenoid bone defects with DTA conferred similar contact mechanics as reconstruction with ICBGs at the time of surgery. Clinical Relevance: This study supports posterior glenoid reconstruction with fresh DTA as a viable alternative solution, with the potential advantage of improving joint congruity via an anatomic reconstruction, resulting in a cartilaginous, congruent articulation with the humeral head. Further studies are required to determine potential clinical effects of the glenohumeral joint contact mechanics reported here.